Caregiver Attendance as a Quality Indicator in the Implementation of Multiple Evidence-Based Practices for Children. Issue 6 (1st November 2020) - Barnett, Miya L.; Lau, Anna S.; Lind, Teresa; Wright, Blanche; Stadnick, Nicole A.; Innes-Gomberg, Debbie; Pesanti, Keri; Brookman-Frazee, Lauren
Abstract : Objective: This study investigated a quality indicator for children's mental health, caregiver attendance in youth psychotherapy sessions, within a system-driven implementation of multiple evidence-based practices (EBPs) in children's community mental health services. Method: Administrative claims from nine fiscal years were analyzed to characterize and predict caregiver attendance. Data included characteristics of therapists ( n = 8, 626), youth clients ( n = 134, 368), sessions (e.g., individual, family), and the EBP delivered. Clients were primarily Latinx (63%), male (54%) and mean age was 11; they presented with a range of mental health problems. Three-level mixed models were conducted to examine the association between therapist, youth, service, EBP characteristics and caregiver attendance. Results: Caregivers attended, on average, 46.0% of sessions per client for the full sample and 59.6% of sessions for clients who were clinically indicated, based on age and presenting problem, to receive caregiver-focused treatment. Following initial EBP implementation, the proportion of caregiver attendance in sessions increased over time. Caregivers attended a higher proportion of youth psychotherapy sessions when clients were younger, had an externalizing disorder, were non-Hispanic White, and were male. Further, higher proportions of caregiver attendance occurred when services were delivered in a clinic setting (compared with school and other settings), by bilingual therapists, and the EBP prescribed caregiver attendance in all sessions. Conclusions: Overall, the patterns of caregiver attendance appear consistent with evidence-informed practice parameters of client presenting problem and age. Yet, several improvement targets emerged such as client racial/ethnic background and service setting. Potential reasons for these disparities are discussed.